2020
DOI: 10.1038/s41598-020-58523-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen immobilization may reduce invasibility of nutrient enriched plant community invaded by Phragmites australis

Abstract: Nutrient enrichment, particularly nitrogen, is an important determinant of plant community productivity, diversity and invasibility in a wetland ecosystem. It may contribute to increasing colonization and dominance of invasive species, such as Phragmites australis, especially during wetland restoration. Providing native species a competitive advantage over invasive species, manipulating soil nutrients (nitrogen) may be an effective strategy to control the invasive species and that management tool is essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…In this study, ammonia increased mostly during the later stage of expansion (from T to G) ( Figures 1B,F,G ), indicating that the final grass dominance over shrub was potentially linked to a more active nitrogen cycle. Compared with perennial shrubs, annual grass species tend to have faster growing rate ( Uddin et al, 2020 ); fast-growing species had higher efficient in transporting water, in acquiring and using nutrients and in fixing carbon ( Reich, 2014 ). Ammonia is released from the decomposition of organic nitrogen, a process conducted by microbes ( Galloway et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, ammonia increased mostly during the later stage of expansion (from T to G) ( Figures 1B,F,G ), indicating that the final grass dominance over shrub was potentially linked to a more active nitrogen cycle. Compared with perennial shrubs, annual grass species tend to have faster growing rate ( Uddin et al, 2020 ); fast-growing species had higher efficient in transporting water, in acquiring and using nutrients and in fixing carbon ( Reich, 2014 ). Ammonia is released from the decomposition of organic nitrogen, a process conducted by microbes ( Galloway et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ammonia is released from the decomposition of organic nitrogen, a process conducted by microbes ( Galloway et al, 2004 ). Moreover, ammonia is easily to be assimilated by fast-growing grass plants ( Uddin et al, 2020 ), which could meet the higher nitrogen demand of grass species and enhance their dominance over shrubs ( Galloway et al, 2004 ). Thus, our results support that enhanced relative P limitation, accompanied by the decreasing TP and increasing TN, potentially altered the relative competence of grass and shrub in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the competition intensity of different target species neighbored by the same neighbor was different from each other (Pérez-Ramos et al 2019;Saccone et al 2017). Secondly, only the factor of plantation condition (grown alone or in mixtures with different neighbors) significantly influenced the root: shoot ratio, which indicated that different neighbors resulted in different nutrition availability for target species or influenced the nutrition absorption of the target species, independently of the soil nutrition conditions (Uddin et al 2020;Zhang et al 2008). Therefore, in the present study, we found several mechanisms potentially contribute to these differential neighbor effects on different target species, as mentioned by other researchers (Bertness and Callaway 1994;Grime, 1977;Grime, 1979;Suding and Goldberg 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented that the lineage-specific control of rhizosphere bacteria and within-lineage bacterial communities was similar among reed communities [ 35 ]. Most studies involving reeds have focused on invading effects [ 36 , 37 ], decomposition efficiency [ 38 , 39 ], and single kingdom or functional groups [ 32 , 40 ]. To the best of our knowledge, the recovery effects on the assemblage stability of the reed rhizosphere microbiome and the vital roles of core taxa and keystone species in maintaining assemblage stability remain unexplored.…”
Section: Introductionmentioning
confidence: 99%